UMP convocation officially ends, 12,174 graduands celebrated throughout 2022 - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA BESAR, 8 November 2022 - The Universiti Malaysia Pahang (UMP) Convocation Ceremony successfully celebrated 12,174 graduands this year through the organisation of three ceremonies involving graduands from 2020, 2021 and 2022.